FAKTOR FAKTOR YANG MEMPENGARUHI KEPATUHAN PEMBATASAN CAIRAN PADA PASIEN HEMODIALISIS BARU DAN LAMA DI RSUD DR. MOEWARDI SURAKARTA - Nurul Jatiningsih; Ratna Wirawati Rosyida; Duwi Pudjiastuti (Rena Cipta Mandiri, 2026)
Background: Hemodialysis is a method of replacing kidney function that uses a device called a dialyzer or artificial kidney. Hemodialysis patients are categorized as new patients (<1 year) while those on hemodialysis are categorized as old patients (>1 year). Differences in fluid restriction compliance are often seen between new and old hemodialysis patients. The purpose of this study was to determine the factors influencing fluid restriction compliance in new and old hemodialysis patients at Dr. Moewardi Hospital, Surakarta. Methods This study used a quantitative research method with a descriptive correlation design and a cross-sectional approach. Sampling used total sampling with 127 respondents at Dr. Moewardi Hospital, Surakarta undergoing hemodialysis. Data analysis used a contingency coefficient. The results showed that analysis of new patients showed a relationship between education, attitudes, family support, and psychological reactions with fluid restriction compliance (p-value 0.000 <0.05). For old patients, there was a relationship between gender, education, knowledge, and attitudes with fluid restriction compliance (p-value 0.000 <0.05). The conclusion of this study is that factors that influence new patients (<1 year) include education, attitude, family support, psychological reactions, while old patients (>1 year) include gender, education, knowledge, attitude.